Perceived stress among undergraduate students during online distance learning: A case study in UiTM Sarawak / Azida Aizin Zainal Abidin, Sumaiyah Syahidah Juanda and Chai Shin Yi - Zainal Abidin, Azida Aizin; Juanda, Sumaiyah Syahidah; Chai, Shin Yi (2021)
The COVID-19 pandemic has impacted the education industry in many ways. Most notably is the shift from in-person educational systems to online and distance learning (ODL). ODL is defined as the use of a variety of platforms that provide education over computer networks, including the internet, email, chat, new groups and messages, and video and audio conferencing (Dhull & Arora, 2019). Even though ODL is not new in higher education, the sudden shift to full ODL has caused issues with not just educators, but also impacted the students intensely. Students claim that the stress is caused by academic, financial, and personal issues, such as their ability to cope with technologies, adequate home facilities for online learning, or consistent internet access especially those in the rural areas (Sahu, 2020). Such burdens can have negative consequences for students' learning and mental health where students may experience lower study motivation, increased independent learning stresses, lack of daily routine which possibly led to higher dropout rates (Wickens, 2011). It was reported in Malaysia that many students have experienced frustration with the online learning mode due to stress, as lecturers seem to delegate more tasks in the e-learning mode as compared to in actual class (Palansamy, 2020). Not only that, but internet connections have also been one of the major problems during ODL where students living in rural areas will have difficulties in attending online lectures and completing their online assessments (Lim, 2020). This was also proven in a study done by Sahu (2020), where it found that students faced difficulty coping with online mode. This includes a student's ability to cope with technologies, adequate home facilities for online learning, or consistent internet access especially those who live in the rural areas.